Moving Toward Implementation of Universal Mental Health Screening by Examining Attitudes Toward School-Based Practices. (May 2022) - Moore, Stephanie A.; Dowdy, Erin; Hinton, Tameisha; DiStefano, Christine; Greer, Fred W.
Universal mental health screening is a proactive approach to identify students who may benefit from prevention or early intervention services. Despite known benefits, few schools are engaging in screening efforts, and it is critical to examine factors that may impede or enhance implementation. Following implementation of a universal screening program across five preschools and elementary schools, this study investigated the attitudes of teachers ( n = 40) and parents ( n = 330) and found strong agreement among stakeholders about the acceptability and appropriateness of universal mental health screening. Teachers and parents expressed less willingness to regularly complete screening forms, yet teachers reported that the Behavior Assessment System for Children–Third Edition: Behavioral Emotional Screening System was a usable screening tool. Implications and future directions to enhance implementation efforts are discussed.